2007
DOI: 10.1126/science.1148992
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Replication Fork Progression Through Histone Supply and Demand

Abstract: DNA replication in eukaryotes requires nucleosome disruption ahead of the replication fork and reassembly behind. An unresolved issue concerns how histone dynamics are coordinated with fork progression to maintain chromosomal stability. Here, we characterize a complex in which the human histone chaperone Asf1 and MCM2-7, the putative replicative helicase, are connected through a histone H3-H4 bridge. Depletion of Asf1 by RNA interference impedes DNA unwinding at replication sites, and similar defects arise fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
535
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 425 publications
(568 citation statements)
references
References 25 publications
31
535
1
1
Order By: Relevance
“…Consistent with this requirement, overexpression of new histones or perturbation of chaperone function both result in replication fork stalling 9 . This implies that when daughter DNA is saturated with new histones, or new histones are not positioned properly, the parental nucleosome at the fork cannot be efficiently transferred and therefore becomes a substantial barrier for replication.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Consistent with this requirement, overexpression of new histones or perturbation of chaperone function both result in replication fork stalling 9 . This implies that when daughter DNA is saturated with new histones, or new histones are not positioned properly, the parental nucleosome at the fork cannot be efficiently transferred and therefore becomes a substantial barrier for replication.…”
Section: Discussionmentioning
confidence: 74%
“…Current views suggest that histone chaperones and nucleosome assembly factors act in a coordinated manner at the replication fork to shuttle parental histones and deposit nascent histones to newly replicated DNA 2,9 . However, this theory is only loosely described and neglects the role of DNA itself, the fundamental component of nucleosome organization and dynamics.…”
mentioning
confidence: 99%
“…We next evaluated the homeostatic levels of single-strand DNA (ssDNA) in matched GICs and non-GICs as assessed by BrDU incorporation under non-denaturing conditions and detected enhanced ssDNA in GIC populations (Supplementary Figure 3b). 34,40,41 We also used the alkaline comet assay to measure DNA strand breaks. GICs had significantly longer tails and higher comet tail DNA content as compared with the non-GICs, indicating the extent of fragmented DNA at baseline was greater in the GICs ( Supplementary Figure 3c-e).…”
Section: Resultsmentioning
confidence: 99%
“…Detection of gH2AX (1 : 500; Abcam, Cambridge, UK) was performed as described previously. 34,40 GICs and non-GICs were grown on GelTrex (Gibco, Invitrogen, Carlsbad, CA, USA)-coated cover slips and treated with DMSO or 10 mM olaparib and left unirradiated or irradiated with 3 Gy and fixed 1, 6, or 24 h after irradiation. Cells were then immunostained for gH2AX.…”
Section: Methodsmentioning
confidence: 99%
“…Structural studies have revealed that Asf1 binds H3-H4 dimers through an H3 interface that is involved in the formation of (H3-H4) 2 tetramers (English et al, 2006). In human cells, it is proposed that Asf1 can disrupt parental nucleosomes (Groth et al, 2007). Furthermore, Asf1 is required for acetylation of histone H3 lysine 56 (H3K56Ac), a mark of newly-synthesized histones that has been found to be important for DNA replication and DNA repair (Recht et al, 2006;Chen et al, 2008;Li et al, 2008).…”
Section: The Function Of Three Histone Chaperones In Rc Nucleosome Asmentioning
confidence: 99%